The relationship of the lucid dreaming ability to mental imagery experiences and skills - Gackenbach, Jayne; Prill, S.; Westron, P. (My University, 1983)
A review of research pertaining to the relationship of waking imagery abilities and experiences to the lucid dreaming ability will be presented. This work includes both spontaneous waking images such as hypnagogic images, hallucinations and daydreams and experimentally produced waking images, such as mental rotation tasks.
Keywords: dreams